2011
DOI: 10.12693/aphyspola.119.1000
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Speech Signal Deformation in Patients after Nasal Septum Surgery (Septolplasty)

Abstract: Nasal blockage belongs to the most common symptoms of nasal diseases in vocal tract area. At the same frequency there appear acoustic symptoms, existing as the change of human voice color. Vocal and articulation disorders of the ear, nose ane throat are usually observed in the form of closed rhinolalia and this observation can be performed both by patients and other listeners as well. Nasal polyps and nasal septum deviation are frequent reason of nasal blockage connected in consequence with decreased nasal ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Consequently, this in turn will result in changes in the vocal tract like increased nasal volume, decreased acoustic damping and increased nasal patency, thereby providing better acoustic space for good resonance [4,20]. The findings of the present study are in consonance with literature [7,10]. However, the findings are contrasting with the results obtained by researchers who did not obtain acoustical changes post-septoplasty [4,21].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Consequently, this in turn will result in changes in the vocal tract like increased nasal volume, decreased acoustic damping and increased nasal patency, thereby providing better acoustic space for good resonance [4,20]. The findings of the present study are in consonance with literature [7,10]. However, the findings are contrasting with the results obtained by researchers who did not obtain acoustical changes post-septoplasty [4,21].…”
Section: Discussioncontrasting
confidence: 64%
“…The authors reported significant improvement in fundamental frequency, amplitude perturbation and frequency perturbation measures after 1 month of recovery from septoplasty [7]. Similarly, Konior and colleagues reported that post-septoplasty there was increased nasal airflow and enhanced perceptual quality of the voice for/n/phoneme [10]. These evidences collectively support there are changes in resonance after surgical management.…”
Section: Introductionmentioning
confidence: 96%
“…The degree of septal deviation from the centre determines the severity of the disorder. 6 Septal deviations affect the free aeration and cause nasal obstruction, blockage, allergic rhinitis and dryness of throat and hence influence the person's quality of life. DNS can lead to sinusitis, affect the sinus drainage and also influence the resonance and voice characteristics of speech.…”
Section: Introductionmentioning
confidence: 99%
“…Deviated nasal septum (DNS) can lead to sinusitis, affect the sinus drainage and also influence the resonance and voice characteristics of speech. Deviated nasal septum can have a significant impact on the quality of the nasal phonemes as well as on nasal airflow (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Effect of septoplasty on 24 individuals with DNS in the age range of 18-49 years was evaluated in a recent study. (1) Participants were selected based on clinical evaluation, active anterior rhinomanometry and digital recording of speech samples. Results indicated improvement in the nasal airflow and in the quality of the nasal phoneme /n/ following surgery.…”
Section: Introductionmentioning
confidence: 99%